Effect of Piperine on Liver Function of CF-1 albino Mice - J. Rao, Peela; D. Kolla, Shoba; Elshaari, Farag; Elshaari, Fatoom; El Awamy, Hayam; Elfrady, Mona; Singh, Rajinder; Belkhier, Asma; Srikumar, Shakila; R. Said, Abdul; J. Dhopoide, Sainath; Ramanujam, Ranjani; et al. (Infectious Disorders - Drug Targets, 2015)
Background: Piperine is isolated from Piper nigrum popularly known as black pepper. Previous studies have demonstrated the beneficial effects of piperine in various health conditions. Additionally, it is a powerful bioenhancer for many drugs. Piperine extract is believed to potentiate the effect of drugs by several folds. The present study is focused on its individual effect on liver function. Materials and methods: A total of 30 CF-1 albino mice obtained from the animal house of faculty of Medicine, Benghazi University, Benghazi, Libya were included in the study. These mice were fed with high cholesterol diet and divided into 2 groups. Twenty mice were administered piperine at a dose of 5mg/kg body weight. Piperine was isolated in Department of Pharmacognosy, Faculty of Pharmacy, Benghazi University, Benghazi and 10 mice were not administered piperine but fed with high fat diet. These mice were anesthetized with ketamine and halothane and blood was drawn from each mouse before the study and after three weeks by cardiocentesis. Serum transaminases (alanine aminotransferase [ALT] and aspartate aminotransferase [AST]), alkaline phosphatase and total protein were measured by authenticated methods. Results: Serum alanine amino transferase was significantly elevated (p=0.0002) in group A mice after the administration of Piperine extract for three weeks compared to those of group B mice. Serum aspartate amino transferase was elevated significantly (p=0.046) and alkaline phosphatase (p= 0.0001) also was significantly increased after the administration of piperine. Serum total protein (p= 0.011) values were significantly decreased after the use of piperine for three weeks in group A mice. Conclusion: This study showed that there might have been a considerable damage to liver with piperine extract. Further research may be required to prove this damage to liver function.
Keywords: piperine